School Climate and Reading Performance Survey Report - Pendleton, Audrey; National Center for Education Statistics (ED), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
A survey examined the relationship between school climate and reading performance using data from the 1983-84 National Assessment of Educational Progress (NAEP) Reading Assessment. The NAEP survey asked a number of questions about possible school problems, such as discipline, teacher commitment, and standards for students. These items were analyzed individually and also combined into a composite measure of school climate. The study revealed that 4th, 8th, and 11th grade students in schools with a better school climate--as measured by the composite measure--tended to score higher on the NAEP Reading Assessment. School climate was more positive in elementary schools, private schools, and schools with lower proportions of students participating in the federal school lunch program. For individual school problems, reading performance was lower for students attending schools where a particular problem was rated more seriously, but association between the severity of a given problem and reading performance disappeared when the background characteristics of students were taken into account. For the composite measure of school climate, based on eight of the school problems, reading performance was higher in schools with a better climate even after controlling for student characteristics. However, the data only show that reading performance and school climate were associated; they cannot demonstrate whether better climate caused higher reading scores. (SR)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Environment; Elementary Secondary Education; Grade 11.; Grade 4.; Grade 8.; Institutional Role; National Surveys; Reading Achievement; Reading Research; National Assessment of Educational Progress; Reports, Evaluative